Analysis methods of forecasting efficiency of investment in innovative projects - Біляєва, Катерина Олександрівна; Соколова, Надія Андріївна (Eastern-European Journal of Enterprise Technologies, 2010)
To assessment of efficiency of innovative projects is applied the combined method, based on neural networks and expert evaluations. It helps improve the quality of forecasts due to increased information content of data compared to the economic and statistical methods.